Investigation of high school students’ social emotional learning skills and social media use - Harun Şahin; Meriç Eraslan; Muhammed Ali Özkan (Frontiers in Psychology)
The current study aims to examine the association between high school students’ social–emotional learning (SEL) skills and their use of social media, as well as to explore potential variations based on certain variables. The research utilized relational and comparative survey methodologies, with 325 high school students participating. Data were gathered through the administration of the “Social Emotional Learning Scale” and the “Social Media Use Scale.” Analytical techniques such as t-tests, ANOVA, and Pearson correlation coefficient were applied to analyze the collected data. The results indicate a slight, adverse connection between the social–emotional learning abilities of students and their utilization of social networking sites. Furthermore, the research revealed that the average ratings for both social–emotional learning abilities and social media usage were moderate. Additionally, no significant differences were observed in social–emotional learning skills and social media use based on gender or grade level.